RESULTS OF GENOTYPING OF STRAINS AND RNA ISOLATES OF TICK-BORNE ENCEPHALITIS VIRUS ISOLATED FROM SICK PEOPLE IN IRKUTSK REGION AND BURYAT REPUBLIC - I. V. Kozlova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Genotyping of nine strains and nine isolates of tick-borne encephalitis virus RNA (TBE) isolated from patients in the Irkutsk Region and. the Buryat Republic in 1963-2009 years conducted. The investigations revealed that three TBE virus genotypes are involved in the etiology of the TBE: Ural-Siberian (genotype 3), Far Eastern (genotype 1) and. European (genotype 2). It is found that the TBE virus of Far East and. Ural-Siberian genotypes can cause disease with a wide spectrum of clinical manifestations: acute TBE (focal and. nonlocal forms), chronic TBE (encephalitic form, progressive course.) Prospects of application of molecular genetic techniques for the rapid indication and. identification of the TBE virus in the blood of sick people are shown.